Circulating tumor cells criteria (CyCAR) versus standard RECIST criteria for treatment response assessment in metastatic colorectal cancer patients - Mayte Delgado-Ureña; Francisco G. Ortega; Diego de Miguel-Pérez; Alba Rodriguez-Martínez; Jose L. García-Puche; Hugh Ilyine; Jose A. Lorente; Jose Exposito-Hernandez; M. Carmen Garrido-Navas; Miguel Delgado-Ramirez; M. José Serrano (Journal of Translational Medicine, 2018)
Abstract Background The use of circulating tumor cells (CTCs) as indicators of treatment response in metastatic colorectal cancer (mCRC) needs to be clarified. The objective of this study is to compare the Response Evaluation Criteria in Solid Tumors (RECIST) with the Cytologic Criteria Assessing Response (CyCAR), based on the presence and phenotypic characterization of CTCs, as indicators of FOLFOX–bevacizumab treatment response. Methods 77 mCRC blood samples from FOLFOX–bevacizumab treated patients were analyzed to isolate CTCs before and after (12 and 24 weeks) treatment, using an immunomagnetic separation method. VEGFR expression was identified by double immunostaining. Results We observed a decrease of CTCs (42.8 vs. 18.2%) and VEGFR positivity (69.7% vs. 41.7%) after treatment. According to RECIST, 6.45% of the patients did not show any clinical benefit, whereas 93.55% patients showed a favorable response at 12 weeks. According to CyCAR, 29% had a non-favorable response and 71% patients did not. No significant differences were found between the response assessment by RECIST and CyCAR at 12 or 24 weeks. However, in the multivariate analysis, RECIST at 12 weeks and CyCAR at 24 weeks were independent prognostic factors for OS (HR: 0.1, 95% CI 0.02–0.58 and HR: 0.35, 95% CI 0.12–0.99 respectively). Conclusions CyCAR results were comparable to RECIST in evaluating the response in mCRC and can be used as an alternative when the limitation of RECIST requires additional response analysis techniques.